Hegel and the Politics of Comedy, Tragedy and Terror - Reid, Jeffrey (Université d'Ottawa | University of Ottawa, 2020)
Greek tragedy, in Hegel’s Phenomenology of Spirit, represents the performative realization of binary political difference, for example, “private versus public”, “man versus woman” or “nation versus state”. On the other hand, Roman comedy and French Revolutionary Terror, in Hegel, can be taken as radical expressions of political in-difference, defined as a state where all mediating structures of association and governance have collapsed into a world of “bread and circuses”. In examining the dialectical interplay between binary, tragic difference and comedic, terrible in-difference, the paper arrives at hypothetical conclusions regarding how these political forms may be observed today.
Keywords: populism; indifference; Greece; Rome; French Revolution; Antigone; politics